Performance Evaluation of Wireless Routing Protocols: RIP and OSPF in WLAN - Muaz, Abdulla; Arun, Dr Kuruvikulam Chandrasekaran (Journal of Applied Technology and Innovation, 2020)
The network layer’s function is to route packets from the source device to the destination device with the help of routers. The routers route the packets using various routing protocols. In this paper, we analyze and compare the routing protocols RIP and OSPF used by routers to see which routing protocol performs better in wireless network in terms of performance. Also, the paper presents the simulation results of these protocol comparisons in terms of throughput and delay.